MODEL PENGEMBANGAN KOMPETENSI SDM BERBASIS ISLAMIC VALUES PADA LEMBAGA KEUANGAN MIKRO SYARIAH - Rini Kurniawati (Jurnal Jurisprudence, 2017)
ABSTRACTThis research is aimed to identify the importance of human resource's role for (keberlangsunhan BMT). Human resource is a main asset that must be take care of in an organization. Their quality shows through knowledge, skill and attitude or competency. Oriented competency to create excellent quality and competitive of human resource. Through recruitment process and pre selection that decided the right minimum standard which supported by organization learning. Those have purpose to create great HR that has professional compentency based on islamic values. Islamic values based on Alquran and Assunah. The frameworks that is proposed hopefully could give and add more knowledges about the importance of HR professional competency development model based in sharia principles on BMT.Keywords: HR competency, recruitment, selection, organization learning, BMT